Mechanical Behavior of Concrete Modified by Replacement of Cement by Rice Husk Ash - M.M. Saravanan; M. Sivaraja (Brazilian Archives of Biology and Technology)
ABSTRACT Construction industry is in need of lump sum quantities of materials which has increased both their demand and price. The use of large quantities of cement leads to increasing CO2 emission and as a consequence, the greenhouse effect. Consumption of wastes and byproducts from various sources in the manufacture of concrete has gained a great deal of importance in present days. Various researches are currently being conducted concerning the use of such products in concrete. RHA is a carbon neutral green product. Lots of ways are being thought of for disposing them by making commercial use of this. Rice husk ash is a good super-pozzolan which can be used to make special concrete mixes. The rice husk ash has been taken for this present study due to its easy availability and effective pozzolonic properties that are expected to improve the mechanical strength properties of concrete. Concrete specimens were made for evaluation of Compressive, Split Tensile, Flexural strength and Stress-Strain Behavior of concrete. The tests were conducted at the age of 7 and 28 days. Generally all mixes containing RHA achieved better properties than the conventional mix without RHA. By the experimental investigation the recommendation is given for using optimum percentage of RHA in concrete.